Prospects for the development of hydrogen power engineering in Tatarstan - A. A. Filimonova; A. A. Chichirov; N. D. Chichirova; A. G. Filimonov; A. V. Pechenkin (Известия высших учебных заведений: Проблемы энергетики)
PURPOSE. Consider the problems and ways of developing hydrogen energy in Russia and in the Republic of Tatarstan. Analyze the main opportunities for the production, transportation, use of hydrogen at the enterprises of Tatarstan. Calculate the economic efficiency of the production of "green" hydrogen by electrolysis at TPP with CCGT in Tatarstan. METHODS. Based on the analysis of literature data and mathematical calculations. RESULTS. Green hydrogen is a promising solution for a decarbonized energy system, and 2020 saw an explosive focus on its use around the world. Tatarstan, as one of the leading economically developed regions of Russia, could take part in the production of "green" hydrogen, the design of electrochemical equipment for its production, the development of technologies for the use of fuel cells, scientific research and training of highly qualified specialists in the field of hydrogen energy. According to the calculations, the production of the most environmentally friendly hydrogen at TPPs with CCGT in Tatarstan will currently cost an average of 2 euros per kilogram, which is significantly lower than the existing market value. CONCLUSION. Tatarstan can become a competitive region for the production and distribution of "green" hydrogen. The main areas of activity should be the production of pure hydrogen, the industrial production of freight transport on fuel cells, the production of megawatt-class electrolysers, the utilization of hydrogen-containing petroleum gases at TPPs in gas turbines or combined cycles with fuel cells.